The World of Wars: Risky Systems – A second-order observation of future wars - Gorm Harste (Nordicum-Mediterraneum, 2014)
The world of the future will not be one without wars. The many hopes we have about a future peace governed by a more or less confederal state will not make wars obsolete. Regular wars and irregular wars will continue and probably on different subjects than we are used to. The article proposes that the form of war will be more about temporalities, i.e. fast interchanges or, rather, more risky protracted wars of attrition and exhaustion and less on tactical well defined territories. The West can neither dominate such wars nor establish one world that is ruled or even governed. The risk is that we have the systems we have. They have their own path dependencies, their temporal bindings and their own stories to tell. In the worst case, the West sticks to an imaginary of almighty power – and then it will lose. We tend to forget that our present past will be experienced and told differently in the future. The “extreme 20th century” will have another history and another impact. Its extremes will be narrated as more extreme, and its temporal bindings become easier to observe. The much celebrated “revolutions in military affairs” will not dominate future war systems. Unipolarity is fading away. Kantian convergences may appear.